2021
DOI: 10.1101/2021.11.17.21266488
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enoxaparin for thromboprophylaxis in hospitalized COVID-19 patients: comparison of 40 mg o.d.vs40 mg b.i.d. The X-COVID19 Randomized Clinical Trial

Abstract: SummaryIt is uncertain whether higher doses of anticoagulants than recommended for thromboprophylaxis are necessary in COVID-19 patients hospitalized in general wards. This is a multicentre, open-label, randomized trial performed in 9 Italian centres, comparing 40 mg b.i.d. vs 40 mg o.d. enoxaparin in COVID-19 patients, between April 30, 2020 and April 25, 2021. Primary efficacy outcome was in-hospital incidence of venous thromboembolism (VTE): asymptomatic or symptomatic proximal deep vein thrombosis (DVT) di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Seventh, we included one study in our analysis that did not yet undergo the peer‐review process. 30 However, sensitivity analyses confirmed that this trial had no significant impact on our main findings.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Seventh, we included one study in our analysis that did not yet undergo the peer‐review process. 30 However, sensitivity analyses confirmed that this trial had no significant impact on our main findings.…”
Section: Discussionmentioning
confidence: 55%
“…Ten studies with a total of 5,753 patients with COVID‐19 were included in the final analysis. 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 More information on the literature search is provided in the flow diagram ( Figure S2 ). Table 1 summarizes the study design of the 10 included trials (further information in Table S3 and S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After abstract screening and full-text reading, 152 RCTs were included in the analysis. All 152 RCTs were posted on the medRxiv server …”
Section: Resultsmentioning
confidence: 99%
“…Our updated analyses included a total of 3808 patients, 3306 patients from the previous report; 253 from HEP-COVID 4 using low-molecular-weight heparin or unfractionated heparin; 66 from the BEMICOP study 5 using bemiparin; and 183 from X-COVID 6 using enoxaparin. Among non-critically ill hospitalized patients, the incidence of all-cause death was 8.0% (157/1962) in the escalated-dose and 8.7% (160/1838) in the standard-dose prophylactic anticoagulation group.…”
mentioning
confidence: 99%